Two couples receive excellent service award in conjunction with UMPSA Quality and Innovation Day 2025 - Siti Nur Azwin, Zulkapri (UMPSA, 2025)
PEKAN, 13 June 2025 – Two married couples from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) received the Excellent Service Award (APC) in conjunction with UMPSA Quality and Innovation Day 2025 (HKI 2025), held festively at the Multipurpose Hall, Pekan.